Análisis comparativo del periodismo digital y los medios impresos y su aceptación entre los estudiantes y docentes de la carrera de Comunicación Social de la UTB - Pérez Jalca, Tifanny Yelena (2020)
This project contains a comparative analysis of the degree of tolerance for the consumption of information in print media such as newspapers, magazines, newsletters, brochures that are embodied in tangible materials and digital journalism such as blogs, websites, online newspapers, social networks or any type of digital platform in which students and teachers of the Social Communication career of the Higher Education Institution Technical University of Babahoyo have access; a variety of definitions of journalism, of mass dissemination media of both traditional and print content and other concepts of interest for the development of research are mentioned; obtaining the data required for the analysis with the resource of the survey applying a questionnaire consisting of a series of questions with multiple choice answers and open and closed answers that facilitate the measurement of the variables that are expressed in quantitative mode to achieve accurate results in order to understand for sure the means by which they obtain the information provided from the written and digital press; As a result, the parametric requirements were met to fulfill the purpose of being of the research to achieve the results required to determine the means most used by the students and the faculty obtained the information.